IMPLEMENTATION OF INDUCTIVE PROCESSES IN GENERAL-PURPOSE EQUIPMENT TO ENHANCE HEAT TRANSFER PROCEDURES - TURCANU, Adrian; NUCĂ, Ilie (Journal of Engineering Science (Chişinău))
The paper explores the energy efficiency of general-purpose installations, particularly the equipment used in espresso coffee production, and the unique functions of hydraulic systems. By applying eco-design principles and innovative, efficient solutions, the negative impact on the environment can be significantly reduced, transforming citizens into eco-consumers. The study aimed to explore ways to decrease energy consumption in hydraulic systems of standard installations, particularly in heat transfer processes in solids and liquids, which account for up to 97% of energy consumption in such installations. An innovative solution is presented that converts electric energy into heat in liquids using inductive heat transfer. The instant heating inductive boiler, based on inductive heat transfer phenomena, eliminates the convective and conductive heat transfer losses associated with the operation of the boiler with the resistive heating element. The design methodology for dimensioning this type of equipment is provided, and the simulation model for necessary verifications in MatLab Simscape is created. With its practical benefits, the new inductive boiler reduces the preheating period to 7.5 s compared to the 90 s of systems with resistive heating elements, thereby eliminating the need to keep the coffee machine at operating temperatures during breaks and providing a reliable solution for energy efficiency.